Tight Oil Accumulation and Enrichment of Chang 7 Oil Layer in Chenghao Area, Ordos Basin Research on Factors - Yin, Lu; Ma, Xiong; Wang, Feng (Scientific Journal of Technology, 2025)
The study of accumulation and enrichment factors for tight oil is a key focus in unconventional petroleum geology. This paper takes the Chang 7 tight oil reservoir of the Yanchang Formation in the Chenghao area, Ordos Basin, Utilizing data from well logging, drilling, and laboratory analysis, it analyzes the conditions of the source rock, reservoir, and caprock, as well as their controlling effects on the quasi-continuous tight oil distribution, to predict favorable zones. Research indicates that the pores in the Chang 7 reservoir in the Chenghao area are predominantly secondary dissolution pores, with an average total plane porosity of 2.5%. Porosity ranges from 0.7% to 12%, with an average of 8.2%, a median of 7.1%, and the main distribution range being 6% to 12%. Permeability ranges from (0.023–1.68)×10^(-3) μm², with an average of 0.16×10^(-3) μm², a median of 0.1×10^(-3) μm², and a main distribution range of (0.1–0.15)×10^(-3) μm², classifying it as a tight reservoir. The reservoir type is quasi-continuous, characterized by lateral connectivity and vertical stacking. The mudstone thickness and hydrocarbon generation intensity of the source rock exhibit significant control over the Chang 7 tight oil, followed by TOC. The porosity and shale content of the caprock show a clear controlling effect on tight oil, followed by permeability, and finally, individual sand body thickness. The shale content of the caprock has a significant controlling effect on tight oil, followed by caprock thickness. Finally, the enrichment factor of the oil layer was used to predict favorable zones for tight oil.